STUDI NILAI ANAK, JUMLAH ANAK YANG DIINGINKAN, DAN KEIKUTSERTAAN ORANG TUA DALAM PROGRAM KB - Hartoyo, Hartoyo; Latifah, Melly; Mulyani, Sri Rahayu (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research was to analyze the correlation between mother and family characteristics with value of children and the influence factors of demand for children and involvement of parent in family planning programme. This research involved 60 families who be acceptor and non-acceptor KB that were selected randomly. Mother’s age had significant correlation with power and influence dimension, working status of mother had significant correlation with stimulation and fun dimension and morality dimension, mother’s education had significant correlation with morality dimension, the number of living children had significant correlation with adult status and social identity dimension and economic utility and security in old age dimension. Moreover, family size variable had significant positive influence to demand for children. Beside that, age of mother’s first marriage and difference of the number of living children with demand for children had significant positive influence to participating family in family planning programme.